Kekuataan Hukum Perjanjian Lisan Antara Agen Kelapa Sawit Dengan Petani - Sri Rumada Sihite; Roulinta Yesvery Sinaga (Pattimura Legal Journal)
Introduction: Oral agreements that occur between oil palm farmers and oil palm agents where the agreement is buying and selling oil palm orally. However, there is a problem where the palm oil agent turns out to be in default. This writing is to examine the oral agreement between oil palm agents and oil palm farmers in Teluk Dalam Village.